Simultaneous visualization of RNA transcripts and proteins in whole-mount mouse preimplantation embryos using single-molecule fluorescence in situ hybridization and immunofluorescence microscopy - Hazra, Rasmani; Spector, David L. (Frontiers in Cell and Developmental Biology, 2022)
Whole-mount single-molecule RNA fluorescence in situ hybridization (smRNA FISH) in combination with immunofluorescence (IF) offers great potential to study long non-coding RNAs (lncRNAs): their subcellular localization, their interactions with proteins in intact mouse embryos, and their function. Here, we describe a step-by-step, optimized protocol, providing optimized conditions, and reagents which allows for the simultaneous detection of proteins and lncRNAs in whole-mount preimplantation mouse embryos. To simultaneously detect proteins and enable RNA probe penetration for the combined IF/smRNA FISH technique, we performed IF before smRNA FISH. We removed the zona pellucida, used Triton X-100 to permeabilize the embryos, and skipped the proteinase digestion step to preserve the antigens. In addition, we modified the IF technique by using RNase-free reagents to prevent RNA degradation during the IF procedure. We also show that compared to embryo sectioning (to 10 µm thickness), the whole-mount method preserves embryo shape, well structure and cellular localization. Using this modified IF/smRNA FISH technique, we have successfully detected Cdx2 protein, a marker of the trophectoderm (TE) lineage, and the lncRNA Platr4 (Pluripotency associated transcript 4), which is expressed in both the TE lineage and inner cell mass. The advantages of this method are that it takes just two days to complete and it can detect moderate to low abundant lncRNA transcripts in whole-mount mouse embryos.